New mouse models for exploring renal tumor extension into the inferior vena cava - Xiubin Li; Huaikang Li; Xupeng Zhao; Jichen Wang; Di Li; Qiuyang Li; Qingjiang Xu; Shengpan Wu; Qiyang Liang; Shangwei Li; Qilong Jiao; Kan Liu; et al. (Communications Biology)
Abstract Renal tumors with inferior vena cava tumor thrombus (IVCTT) remain a challenge in urology. However, in vivo models remain unavailable, which hampers the elucidation of its pathogenesis, identification of therapeutic targets, and screening for effective drugs. In this study, we initially develop two IVCTT models in BALB/c and BALB/c-nu/nu mice using the mouse Renca cell line. The pathological features and immune microenvironment of IVCTT in immunocompetent mice closely resembles those observed in humans. Single-cell transcriptome sequencing, immunohistochemistry and multiplex immunohistochemistry reveal a predominance of monocytes, macrophages, and neutrophils within IVCTT, mirroring the cellular composition of the human IVCTT; however, fewer lymphocytes are observed. The IVCTT in immunodeficient mice progresses much faster than in immunocompetent mice. More importantly, we successfully use the human tumor cell line on the BALB/c nu/nu mice to create an IVCTT model. The proposed in vivo models mimic the progression of renal tumors with IVCTT, clarify that the immune system can inhibit tumor thrombus progression, and provide tools for subsequent mechanistic research and translational preclinical studies.